2020
DOI: 10.1111/ldrp.12228
|View full text |Cite
|
Sign up to set email alerts
|

A Multifactorial Model of Dyslexia: Evidence from Executive Functions and Phonological‐based Treatments

Abstract: In this research, we examined the responsiveness to treatment in 49 Italian children with Dyslexia. In part A, we compare the efficacy of a phonological‐based treatment (Ph‐T) with a cognitive training of executive functions (CT). In part B, we investigate whether a sequential treatment (CT+Ph‐T) has a larger remedial effect compared to the pure phonological‐based treatment (Ph‐T + Ph‐T). Results after 24 hours of treatment showed significant improvements in the executive functions (EFs) for the sequential gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 65 publications
0
15
0
1
Order By: Relevance
“…Recently, Cancer and collaborators (Cancer et al, 2020) also showed that a rhythmic intervention program was as efficient as a program combining two yet validated treatments for dyslexia (Bakker’s Visual Hemisphere-Specific Stimulation and the Action Video Game Training), even if the effect of each training program was more evident for different aspects of reading. Training executive functions also seems to improve reading skills in DD (Pasqualotto & Venuti, 2020), but the effect has never been compared with that of a rhythmic training program. Further investigations are needed, considering interindividual differences in dyslexia, to tailor interventions to each individual’s skills.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cancer and collaborators (Cancer et al, 2020) also showed that a rhythmic intervention program was as efficient as a program combining two yet validated treatments for dyslexia (Bakker’s Visual Hemisphere-Specific Stimulation and the Action Video Game Training), even if the effect of each training program was more evident for different aspects of reading. Training executive functions also seems to improve reading skills in DD (Pasqualotto & Venuti, 2020), but the effect has never been compared with that of a rhythmic training program. Further investigations are needed, considering interindividual differences in dyslexia, to tailor interventions to each individual’s skills.…”
Section: Discussionmentioning
confidence: 99%
“…In adults as well as children, cognitive training has been found to improve working memory, attention skills, inhibition skills, problem-solving abilities, and cognitive flexibility [45][46][47]; for a recent review, see [48]. More importantly, it has provided encouraging results on dyslexia remediation with a sample of Italian-speaking children (8-14 years old) [49]. After regular training over five weeks with 30 min of daily exercises, these children showed significant improvements in attention and working memory, inhibition ability, visual-motor integration skills, cognitive flexibility, and fluid intelligence.…”
Section: Developmental Dyslexiamentioning
confidence: 99%
“…La alteración en la MT fonológica es un predictor cognitivo en los niños con dislexia, a diferencia de la MT no verbal, que parece estar conservada, lo que sugiere que el rendimiento de la MT es un indicador del potencial de aprendizaje, basado en conocimientos previos adquiridos en los diferentes contextos (Barbosa et al, 2019). El entrenamiento cognitivo de los componentes de las FE y conciencia fonológica en niños con dislexia demuestra un progreso en la atención visoespacial, MT, precisión y velocidad lectora, favoreciendo la fluidez, comprensión de textos escritos, el funcionamiento de la ruta sub léxica y el reconocimiento rápido de palabas a través de la ruta léxica; estos procesos se complementan entre sí, sin embargo, los ejercicios cognitivos parecen ser más efectivos que los de base fonológica (Pasqualotto & Venuti, 2020). El efecto del entrenamiento del programa de aceleración de lectura sobre las FE en dominios no lingüísticos permitió el análisis electro-físico en las tareas de organización de fichas de Wisconsin antes y durante ocho (8) semanas de entrenamiento.…”
Section: Características De Las Fe En El Teapzunclassified